(3cJGH GdEdeGY Edi eYQaI CUhd GdQhGjI (B,(3JbbjO GdSeGY hLed ef aVGFd GdMOjK hGgdg hfcJ ef BOGH MedJg hfbdJgs - (3YjGV Hf ehSi Hf YjGV Hf YeQhf GdjMUHj GdSHJj, CHh GdaVd,J (B544 (3g` s ((3Ydj Hf eMeO Hf Ydj Hf aQL s)
(3ChdgG (B:s
(3hHYO CjgG GdQGZH aj VH GdYfGjI Edi JdNjU aUhd eYQaI GdVHW hJbjjO GdSeGY hGdQhGjI hJHjf GfhGYgG s
(3BNQgG (B:s
(3dCHUQJ CeTj Ydi eGJHjfJ GdTLQ MJi jPgH GdaLQ s
(3GdfSNI HgG MhGTs
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B99 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B16s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B158s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs